Convergence results for controlled contractions and applications to a system of Volterra integral equations - Lifang Guo; Mudasir Younis; Haroon Ahmad; Mahpeyker Özturk; Fahim Ud Din; Shahbaz Ahmad (Applied Mathematics in Science and Engineering)
This work presents the concept of controlled dislocated metric spaces, and the Banach contraction principle in these spaces is examined. Next, we provide extensive examples of numerical convergence of fixed points to demonstrate the practical implications of such spaces. Along with specific instances, it presents the idea of a rational contraction of the [Formula: see text]type to determine common fixed points in such spaces. Moreover, numerical analysis and graphical comparisons are used to further assess the existence of common fixed points based on the provided notions. Lastly, using these ideas to solve a Volterra integral equation shows how useful they are for finding common solutions, improving our comprehension of fixed point theory in these spaces, and creating new avenues for applications.